2014
DOI: 10.1185/03007995.2014.908829
|View full text |Cite
|
Sign up to set email alerts
|

Real-world patterns of endocrine therapy for metastatic hormone-receptor-positive (HR+)/human epidermal growth factor receptor-2-negative (HER2−) breast cancer patients in the United States: 2002–2012

Abstract: Fewer than two thirds of patients initiated treatment for HR+/HER2- mBC with ET. Among those who did, most received only one line of ET before discontinuation or transition to CT. Patients who received multiple lines of ET experienced shorter durations of therapy with each line. Real-world treatment with ET falls short of the targets recommended by guidelines, representing unmet need for treatment options that improve the effectiveness of endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 25 publications
5
34
2
3
Order By: Relevance
“…When palliative ET was administered, the patients received a median of 2 lines of ET. This result is in line with those reported in previous studies [13,14]. The median duration of ET was 18 months.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When palliative ET was administered, the patients received a median of 2 lines of ET. This result is in line with those reported in previous studies [13,14]. The median duration of ET was 18 months.…”
Section: Discussionsupporting
confidence: 83%
“…Of some younger patients (12% of the cohort), nearly all had had prior adjuvant ET, and most of them had visceral metastases at first diagnosis of metastatic disease, so that the attending oncologists subsequently had no confidence in further ET lines and only chemotherapy was used during the further palliative disease course. Previous clinical practice studies analyzing palliative therapy in HR-positive BC excluded patients who had no systemic therapy and analyzed only those who received a therapy [10,11,12,13,14]. However, in order to describe the entity HR-positive metastatic BC accurately and comprehensively, it is important to also report the cases in which systemic therapies had not been used.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that few patients received three lines of endocrine therapy as suggested by NCCN guidelines, and concluded that single-agent endocrine therapy may not be as effective beyond first line, given most patients received less than three lines of endocrine therapy before receiving chemotherapy and the median future science group www.futuremedicine.com duration of endocrine therapy decreased from first to second line. Swallow et al [35] evaluated the real-world patterns of endocrine therapy for HR-positive/HER2-negative mBC in 19,120 postmenopausal mBC patients in the USA from 2002 to 2012. The authors examined mean numbers of lines of therapy and median duration of each line using the MarketScan commercial health insurance claims database (2002Q3-2012Q2).…”
Section: Overview Of Treatment Patterns Studiesmentioning
confidence: 99%
“…Ten of these were retrospective chart reviews [29,30,[32][33][34]37,38,41,44,45], two were physician surveys [31,46] and six were analyses of secondary databases (e.g., Surveillance, Epidemiology and End Results [SEER]-Medicare database, commercial claims) [35,36,39,40,42,43]. These studies examined a variety of therapeutic options, including endocrine therapy, chemotherapy and surgery.…”
Section: Overview Of Treatment Patterns Studiesmentioning
confidence: 99%
“…A retrospective chart review of patients with recurrent or de novo HR-positive/HER2-negative MBC, treated at 13 oncology practices in the US, found that ET was used as first-line treatment in only 68%, and only about 7% received 3 lines of ET before chemotherapy was initiated [11] . Another analysis of 19,120 women with HR-positive/HER2-negative MBC reported that only 60% received initial ET and only 26% received secondline ET [12] . This article reviews approved and emerging ET options and available data regarding their impact on QoL in patients with HR-positive MBC, including those with visceral disease.…”
mentioning
confidence: 99%